Effect of a national requirement to introduce named accountable general practitioners for patients aged 75 or older in England: regression discontinuity analysis of general practice utilisation and continuity of care - Barker, Isaac (BMJ Open, 2016)
OBJECTIVE: To assess the effect of introducing named accountable general practitioners (GPs) for patients aged 75 years on patterns of general practice utilisation, including continuity of care. DESIGN: Regression discontinuity design applied to data from the Clinical Practice Research Datalink to estimate the treatment effect for compliers aged 75. SETTING: 200 general practices in England. PARTICIPANTS: 255 469 patients aged between 65 and 85, after excluding those aged 75. INTERVENTION: From April 2014, general practices in England were required to offer patients aged 75 or over a named accountable GP. This study compared having named accountable GPs for patients aged just over 75 with usual care provided for patients just under 75. OUTCOMES: Number of contacts (face-to-face or telephone) with GPs, longitudinal continuity of care (usual provider of care, or UPC, index), number of referrals to specialist care and numbers of common diagnostic tests. Outcomes were measured over 9 months following assignment to a named accountable GP and for a comparable period for those unassigned. RESULTS: The proportion of patients with a named accountable GP increased from 3.5% to 79.8% at age 75. No statistically significant effects were detected for continuity of care (estimated treatment effect 0.00, 95% CI −0.01 to 0.02) or the number of GP contacts per person (estimated treatment effect −0.11, 95% CI −0.31 to 0.09) over 9 months. No significant change was seen in the number of referrals, blood pressure or HbA1c diagnostic tests per person. A statistically significant treatment effect of −0.05 cholesterol tests per person (95% CI −0.07 to −0.02) was estimated; however, sensitivity analysis indicated that this effect predated the introduction of named accountable GPs. CONCLUSIONS: Continuity of care is valued by patients, but the named accountable GP initiative did not improve continuity of care or change patterns of GP utilisation in the first 9 months of the policy.